X-Rays and Cancer Detection: Screening, Diagnosis, and Monitoring - Majeda Raja Saeed Albalwi; Abeer Ali Alharbi; Ali Yahya Kaabi; Salman Hamed H. Al-Sulami; Saqer Obadallah S Aljohani; Ali Saad Altukhais; Fahad Eid Salem Alotaibi; Abdul Aziz Mubarak Barak Al-Otaibi; Abdul Malik Abdullah Al-Issa; Khaled Musa Al-Otaibi (International Journal of Medical Toxicology and Legal Medicine, 2024)
The study explores the pivotal role of X-ray technology in the comprehensive management of cancer through a detailed analysis of existing secondary data. With cancer remaining a leading cause of morbidity and mortality worldwide, efficient screening and diagnostic methodologies are essential. This study evaluates the efficacy, accuracy, and limitations of X-ray procedures in the early detection, diagnosis, and ongoing monitoring of various cancer types. Utilizing a range of secondary data sources, including peer-reviewed journals, medical databases, and clinical trials, the study synthesizes current findings to assess X-rays’ contributions to medical imaging and patient outcomes. The findings underline the importance of X-rays as a non-invasive, cost-effective tool in clinical settings, despite challenges related to sensitivity and radiation exposure. Moreover, the study highlights advancements in digital radiography and the integration of artificial intelligence, which promise enhanced diagnostic precision. This comprehensive examination offers valuable insights for healthcare professionals and policymakers aiming to optimize cancer detection and management strategies, while also considering the implications for patient safety and healthcare resource allocation.